Zoonoses research in Somalia: A scoping review using a One Health approach - Mumin, F.I.; Fenton, A.; Osman, A.Y.; Mor, Siobhan M. (Elsevier, 2023)
Zoonoses are likely to cause a substantial burden on both human and animal health systems in Somalia, given the close proximity between the pastoralist majority and their livestock. However, decades of instability leading to weak disease surveillance have meant that data on the burden of zoonoses is lacking. The aim of this scoping review was to assess and synthesize the available literature on the presence and burden of zoonoses in Somalia.